2001
DOI: 10.4049/jimmunol.166.7.4737
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Early Alcohol-Induced Liver Injury in CD14-Deficient Mice

Abstract: Activation of Kupffer cells by gut-derived endotoxin is associated with alcohol-induced liver injury. Recently, it was shown that CD14-deficient mice are more resistant to endotoxin-induced shock than wild-type controls. Therefore, this study was designed to investigate the role of CD14 receptors in early alcohol-induced liver injury using CD14 knockout and wild-type BALB/c mice in a model of enteral ethanol delivery. Animals were given a high-fat liquid diet continuously with ethanol or isocaloric maltose-dex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
125
1
3

Year Published

2004
2004
2009
2009

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(137 citation statements)
references
References 45 publications
8
125
1
3
Order By: Relevance
“…This may be owing to inhibition of NF-kB activity by activated GR or heat-shock transcription factor (Szabo and Mandrekar, 2002). Another investigation indicated that CD14, a TLR co-receptor present on myeloid cells, has an important function in chronic alcohol-induced liver damage, because chronic ethanol feeding caused more severe liver injury in wild-type mice rather than in CD14 knockout mice (Yin et al, 2001), supporting the hypothesis that endotoxin acts through CD14 and TLR4 in the development of early alcohol-induced liver injury (Seki et al, 2007).…”
Section: Chronic Alcoholic Hepatitismentioning
confidence: 99%
“…This may be owing to inhibition of NF-kB activity by activated GR or heat-shock transcription factor (Szabo and Mandrekar, 2002). Another investigation indicated that CD14, a TLR co-receptor present on myeloid cells, has an important function in chronic alcohol-induced liver damage, because chronic ethanol feeding caused more severe liver injury in wild-type mice rather than in CD14 knockout mice (Yin et al, 2001), supporting the hypothesis that endotoxin acts through CD14 and TLR4 in the development of early alcohol-induced liver injury (Seki et al, 2007).…”
Section: Chronic Alcoholic Hepatitismentioning
confidence: 99%
“…It has been shown in animal experiments that both the administration of antibiotics to reduce endotoxemia and the inactivation of Kupffer cells with gadolinium chloride prevent liver injury (Thurman, 1998). CD 14 or CD 14-coupled toll like receptor 4 knockout mice with less TNF-a production are also resistant to alcohol toxicity Yin et al, 2001). Furthermore, inhibition of TNF-a by TNF-a antibodies or by the use of a TNF-a receptor knockout mouse model also protects against alcohol-induced liver injury (Hines and Wheeler, 2004).…”
Section: Alcohol and Inflammationmentioning
confidence: 99%
“…These mice are resistant to endotoxin effects and show no signs of chronic alcohol induced liver injury compared to wild type mice that develop severe alcoholic hepatitis (Uesugi et al, 2001). Other experimental models that lacked CD14 or LBP also demonstrate that LPS-mediated signaling pathways are critical for alcoholic liver injury (Yin et al, 2001). On LPS induction, early growth response-1 (Egr-1), another transcription factor, signals through MAPK (Erk1 ⁄ 2) via TNF-a in hepatic macrophages on chronic alcohol exposure (Kishore et al, 2002).…”
Section: Lps-tlr-4-mediated Signalingmentioning
confidence: 99%